Das tramas do mito aos (des)caminhos da história: a travessia do herói nas literaturas cervantiana e rosiana - COLLINGE, Márcia Denise da Rocha (Universidade Federal do Pará, 2019)
The present thesis consists of comparative research whose focus is the formation of two heroes in Quixote (1605/1615), by Miguel de Cervantes (1547-1616), and Grande sertão: veredas (1956), by Guimarães Rosa (1908-1967), in order to reveal the protagonist Riobaldo as a figure analogous to the “Knight of the Sad Countenance”, by circumventing the tradition of mythical heroism. From the paradigm of the tradition of “La Mancha,” that links the chief Urutú Branco and the Knight of the Lions, resonates echoes of deities; of mythical characters and of conceptual references from classical and medieval sources. I defend the proposition that Quixote recovers mythology that reverberates as an ironic concept and acts as the genesis of the novel whose genre, especially by the recomposition of archaic roots in the creation of a hero, transforms it into a modern myth in two ways: 1) proclamation of ancient wisdom, 2) the justification and rewriting of the cultural history of a nation. Through this, I apply the presuppositions of the literary remythification, proposed by Eleazar Mielietinski (1918-2005), for the elaboration of the everyman hero in the corpora texts. Therefore, I interact with the mythical figure of the hero after the ritual of consecration in the studies of the mythology, aligned with the thought of intellectuals such as Joseph Campbell (1904-1987) and Gustav Jung (1875-1961). From the dialogue proposed between these and other interpreters, I decipher between the various faces of the hero in a historical-artistic investigation, from the myth in its classical form, such as the epic and the tragedy, to its medieval, baroque and romantic developments. In the exegesis of the works, I present the metamorphosis of the literary myth Don Quixote, whose journey leaves an indelible mark on the universal heroic mosaic — the eternal image. The depth of this study reveals how the ingenious knight stands out in the memory of Brazilian literature, ratifying the various manifestations of empowerment of Cervantine themes, especially in the work of Guimarães Rosa, who sees, in Cervantes’ genius, dimensions for a new system of the creation of different types of heroes — madmen in streaks, full of lucid intervals in the deceptive Sertão of Minas Gerais. I exhibit, through the actions of the knight Tatarana, clear and enigmatic trademarks of La Mancha, among which I emphasize: 1) mature birth 2) cycles and saga resulting from the search for adventure 3) the psychological evolution 4) the myth of the duo 5) the admiration of the lady-knight 6) Love as fantasy 7) the ambivalent battles marked by ritual 8) the return of heroes 9) mad narration 10) the disillusion of darkness and light. Through this work, I establish the idea of “Rosian Quixoticism,” an innovative approach to Rosian criticism from a quixotic reading of the novel. It is Riobaldo, heir to the lineage of Achilles, Odysseus, Oedipus, Amadis de Gaula, Palmeirim of England, Don Quixote and Roque Guinart who, in embodying contradictory values mixing chivalrous ideals and problematic conflicts in a world in absentia, establishes the message of the mythical hero, the human being, in the traversal of “the last classic”. Accordingly, I see the expansion of the Rosian critical fortune, as well as the expansion of tradition of La Mancha in Brazil through the “endless aesthetic-receptive adventure” transmuted into the veiling and unveiling of the mythical faces of these heroes, true literary metamorphoses: Don Riobaldo Manchego and the jagunço, Quixote.